Intercalation of Coordinatively Unsaturated FeIII Ion within Interpenetrated Metal–Organic Framework MOF‐5. Issue 23 (26th April 2016) - Holmberg, Rebecca J.; Burns, Thomas; Greer, Samuel M.; Kobera, Libor; Stoian, Sebastian A.; Korobkov, Ilia; Hill, Stephen; Bryce, David L.; Woo, Tom K.; Murugesu, Muralee
Abstract: Coordinatively unsaturated Fe III metal sites were successfully incorporated into the iconic MOF‐5 framework. This new structure, Fe III ‐ i MOF‐5, is the first example of an interpenetrated MOF linked through intercalated metal ions. Structural characterization was performed with single‐crystal and powder XRD, followed by extensive analysis by spectroscopic methods and solid‐state NMR, which reveals the paramagnetic ion through its interaction with the framework. EPR and Mössbauer spectroscopy confirmed that the intercalated ions were indeed Fe III, whereas DFT calculations were employed to ascertain the unique pentacoordinate architecture around the Fe III ion. Interestingly, this is also the first crystallographic evidence of pentacoordinate Zn II within the MOF‐5 SBU. This new MOF structure displays the potential for metal‐site addition as a framework connector, thus creating further opportunity for the innovative development of new MOF materials. Abstract : Coordinatively unsaturated Fe III metal sites were successfully incorporated into the iconic MOF‐5 framework. This new structure, Fe III ‐ i MOF‐5, is the first example of an interpenetrated MOF linked through intercalated metal ions, which displays the potential for metal‐site addition as a framework connector, thus creating further opportunity for the innovative development of new MOF materials.